ERP Implementation Assessment in the Manufacturing Industries - Kanchymalay, K; Arif, F.; Hashim, U. R.; Amirrudin, S. (2011)
This study was aimed to explore and assess the implementation processes of Enterprise Resource Planning (ERP) system in the manufacturing industries in Melaka, Malaysia which included the implementation methodology and the problems encountered in the post implementation stage. The study shows that companies chosen for this study have used a proper and detailed project planning with appropriate implementation methodology for a successful ERP implementation. This study also marks an initial effort to assess the ERP implementation in the manufacturing industries in Melaka, Malaysia.